Perinatal management of gastroschisis - Vincenzo Insinga; Clelia Lo Verso; Vincenzo Antona; Marcello Cimador; Rita Ortolano; Maurizio Carta; Simona La Placa; Mario Giuffrè; Giovanni Corsello (Hygeia Press di Corridori Marinella, 2014)
Gastroschisis is an abdominal wall defect, typically located to the right of the umbilical cord, requiring an early surgical treatment shortly after birth. Affected patients can be identified during intrauterine life with US and should be delivered in referral hospitals where a multisciplinary approach can be provided, involving neonatologists, clinical geneticists, surgeons and other specialists. These patients require a complex management in Neonatal Intensive Care Unit (NICU) and a long term follow-up after discharge. Exceed the acute neonatal condition, gastroschisis has a good prognosis, if there are no overlapping complications, and it should be differentiated from omphalocele, burdened with worse prognosis, and other conditions in the wide spectrum of abdominal wall defects.